The Hirschsprung's-multiple endocrine neoplasia connection - Sam W. Moore; Monique Zaahl (Clinics, 2012)
The risk of patients with Hirschsprung's disease later developing multiple endocrine neoplasia remains a matter of concern. The multiple endocrine neoplasia 2-Hirschsprung's disease association has been shown to cosegregate in Hirschsprung's disease patients with both short- and long-segment aganglionosis, although patients with long-segment aganglionosis a to carry the greatest risk. The Hirschsprung's disease-medullary thyroid carcinoma relationship also appears to be bi-directional, and activation or suppression of the rearranged during transfection gene appeared to vary over succeeding generations within the same family. Rearranged during transfection gene variations are associated with both conditions. The cosegregation of Hirschsprung's disease and multiple endocrine neoplasia 2 is particularly interesting as it involves both "switch off" and "switch on" of the rearranged during transfection proto-oncogene in the same patient. This cosegregation mostly relates to the cysteine-rich area on RET620 (the "Janus gene"). The mechanism whereby rearranged during transfection influences gene activation in multiple endocrine neoplasia 2 is complex, but genetic variations impair the rearranged during transfection tyrosine kinase response to tyrosine kinase activation, thus appearing to dictate downstream signaling cascade responses. Better understanding of the RET-620 relationship allows for a more cost-effective method of identifying those at risk by focusing rearranged during transfection gene testing to this specific area as a "hot spot". The clinical awareness of possible medullary thyroid carcinoma has led to timely intervention and early treatment of this chemo- and radioresistant tumor with poor prognosis. Establishment of "risk" by genetic testing has become a classic model of molecular medicine being integrated into patient care and offering rearranged during transfection directed prophylactic surgical management. In addition, novel approaches to treatment based on this genetic knowledge have already shown early promise in randomized clinical trials.